2006
DOI: 10.1111/j.1365-2699.2006.01522.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting functional traits maintain lichen epiphyte diversity in response to climate and autogenic succession

Abstract: Aim  Lichen epiphytes are important for biodiversity conservation and are also widely applied as environmental indicators. However, biogeographical and ecological knowledge underpinning lichen epiphyte conservation, and the use of lichens as indicators, is based primarily on a limited range of ‘macrolichen’ species. Wider trends in epiphyte biodiversity remain largely unexplored. This paper examines the community structure of lichen epiphytes on aspen (Populus tremula L.) in Scotland, including species across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
3
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 72 publications
5
78
3
4
Order By: Relevance
“…A typical habitat dominated by various ombrophobous and aerohygrophilous microlichens consists of dry bark of forest trees in old growth stands (Barkman 1958;Holien 1998). Ellis & Coppins (2006) showed that effects of F. 5.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A typical habitat dominated by various ombrophobous and aerohygrophilous microlichens consists of dry bark of forest trees in old growth stands (Barkman 1958;Holien 1998). Ellis & Coppins (2006) showed that effects of F. 5.…”
Section: Discussionmentioning
confidence: 99%
“…For example, size and age of trees may have different effects on richness or frequency of macro-and microlichens (Ihlen et al 2001;Ellis & Coppins 2006). In general, succession of epiphytic lichen communites starts with crustose lichens, followed by foliose lichens and, eventually, fruticose lichens (Ochsner 1927;Barkman 1958;Ellis & Coppins 2006). At least in one of the two best models the number of trees with DBH>36 cm had a negative effect on microlichen richness, which can be seen as a confirmation of the general successional trend.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In short, epiphytic macrolichens were systematically examined on a 0.378 ha plot for up to 2 h. We did not sample microlichens (crustose forms) as they are not easily distinguished for purposes of a national monitoring system (McCune, 2000;Will-Wolf, 2002) and they appear to comprise a minor component of the local epiphytic flora; in contrast to the greater diversity of crustose species found at some riparian sites (Carmer, 1975) or in moister environments on European aspen (Lipnicki, 1998;Ellis and Coppins, 2006). Only species occurring on woody substrates at least 0.5 m above the forest floor were sampled.…”
Section: Plot Selection and Field Methodsmentioning
confidence: 99%